(untitled) (The Research of Medical Science Review, 2025)
Background: Late-onset fetal growth restriction (FGR), diagnosed after 32 weeks of gestation, poses diagnostic challenges due to its subtle clinical presentation and less overt placental pathology compared to early-onset FGR. Distinguishing pathologically growth-restricted fetuses from constitutionally small ones is crucial for improving perinatal outcomes, especially in low-risk pregnancies. Birth of healthy term infant depends on normal placental development with its disturbance causing problems like fetal Growth Restriction (FGR). Objective: To compare placental morphological and histopathological features between late-onset FGR and appropriately grown (AGA) fetuses in low-risk pregnancies. Methods: A prospective, cross-sectional case-control study was conducted at Fatima Memorial Hospital, Lahore in Maternal fetal Medicine Unit from November 2024 to April 2025. Placentas of ninety-one low-risk pregnancies complicated by late-onset FGR were compared with placentas of 91 gestational age-matched AGA pregnancies. Placentas were examined for gross [morphological] and histopathological abnormalities, including maternal vascular malperfusion, distal villous hypoplasia, infarction, and cord insertion anomalies. Data was analyzed using SPSS 25 with appropriate statistical tests. Results: FGR placentas had significantly lower weight (41.75% <10th percentile vs. 4.4% in AGA; p < 0.0001) and a higher fetal-placental weight ratio. Marginal cord insertion was more frequent in FGR (97.8% vs. 46.15%; p < 0.0001). Histologically, maternal vascular malperfusion (57.14% vs. 9.89%), distal villous hypoplasia (45.05% vs. 6.59%), and infarction/intervillous thrombi (20.88% vs. 2.2%) were significantly more common in FGR placentas. Villous changes related to maternal under perfusion were more prevalent in placentas of fetuses with severe FGR [EFW <3rd percentile] or FGR with EFBW between 3-10th centile with abnormal Dopplers.